CHARACTERISTIC OF WIND PROFILES IN TROPICAL TROPOPAUSE LAYER ASSOCIATED WITH QBO-MJO CONNECTION: AN EAR OBSERVATION - Nabilatur Rosyidah, Arlif
The Madden-Julian Oscillation (MJO) is a large-scale convective system that propagates eastward. A recent study found that during boreal winter, 40% of the variability of MJO is related to QBO. The main feature of QBO influence on the troposphere is through changes in the characteristics of the Tropical Tropopause layer (TTL), a transition layer between the troposphere and stratosphere. This study aims to examine wind variation in TTL and confirm the tropopause dynamics associated with QBO and its effect on the MJO convective activity. The parameters analyzed in this study are 3D wind and Radar Tropopause (RT) height obtained from the Equatorial Atmosphere Radar (EAR) with high vertical resolution (150 m). Convective activity analysis was carried out based on the parameters of precipitation, OLR, and Convective Available Potential Energy (CAPE) from radiosonde data based on the EAR zonal wind index for QBO. EAR observations confirmed the variation in TTL dynamics due to QBO. In the area around the tropopause, the zonal wind shear is smaller at QBOE which is associated with a perturbation temperature of -2°C at an altitude of 16-18 km as a consequence of changes in the zonal wind from the quasi-geostrophic of the thermal wind balance. This variation triggers a vertical upward motion which is indicated by a vertical wind profile. The height of the tropopause increased at 17.4 km compared to QBOW and QBON which were valued at 16.7 km and 16.8 km, respectively. The TTL characteristic should support increased convective activity during QBOE. However, the composite of precipitation on the MJO during QBOE and QBOW did not have a significant difference so that the TTL characteristics did not significantly affect the MJO convection activity around West Sumatra.